Intermediate accounting vol.3 - Valix, Conrado T. (Manila : GIC Enterprises & Co., Inc., 2021)
This book is the culmination of the Intermediate accounting cluster. It is designed to cover the preparation of statement of financial position, income statement, statement of comprehensive income, statement of changes in equity, statement of cash flow, notes to financial statements related parties and events after reporting period.
1. Financial statements -- 2. Statement of financial position -- 3. Notes to financial statements -- 4. Statement of comprehensive income -- 5. Statement of changes in equity -- 6. Noncurrent asset held for sale -- 7. Discontinued operation -- 8. Accounting changes -- 9. Interim financial reporting -- 10. Operating segment -- 11. Derivatives -- 12. Derivatives -- 13. Biological asset -- 14. Cash and accrual basis -- 15. Single entry -- 16. Error correction -- 17. Statement of cash flow -- 18. Book value per share -- 19. Basic earnings per share -- 20. Diluted earnings per share -- 21 Diluted earnings per share -- 22. Hyperinflation -- 23. Current cost accounting -- 24. SMEs - definition -- 25. SMEs - financial statements -- 26. SMEs - assets -- 27. SMEs - assets - 28. SMEs - liabilities -- 29. SMEs - equity -- 30. Small entities.
Keywords: ACCOUNTING